Dataset for: How does emotional intelligence help teachers to stay engaged? Cross-validation of a moderated mediation model. - Mérida-López, Sergio; Bakker, Arnold Bastiaan; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
This study used job demands–resources and emotional intelligence theories to test a moderated mediation model explaining work engagement in two independent teacher samples. We hypothesised that emotional intelligence buffers the effect of emotional demands on work engagement through self-appraised stress. Childhood and primary educators (sample 1, N=351) and secondary educators (sample 2, N=344) participated in the study. Although emotional intelligence did not moderate the relationship between emotional demands and self-ap- praised stress, it did buffer the relationship between self-appraised stress and work engagement in both teacher samples. The findings suggest that emotional intelligence has a specific buffering effect affecting intrapersonal and interpersonal processes. We discuss the implications of these findings for efforts to help teachers deal with the detrimental effects of stress on work engagement.
Dataset_teachers_demands_engagement.
Keywords: Inteligencia emocional; Profesores - Estrés laboral; Emotional demands; Self-appraised stress; Work engagement; Emotional intelligence; Moderated mediation